Concerns and professional development needs of science faculty at Taibah university in adopting blended learning - Al-Sarrani, Nauaf (Kansas State University, 2010)
The purpose of this study was to obtain science faculty concerns and professional development needs to adopt blended learning in their teaching at Taibah University. To answer these two research questions the survey instrument was designed to collect quantitative and qualitative data from close-ended and open-ended questions. The participants’ general characteristics were first presented, then the quantitative measures were presented as the results of the null hypotheses. The data analysis for research question one revealed a statistically significant difference in the participants’ concerns in adopting BL by their gender sig = .0015. The significances were found in stages one (sig = .000) and stage five (sig = .006) for female faculty. Therefore, null hypothesis 1.1 was rejected (There are no statistically significant differences between science faculty’s gender and their concerns in adopting BL). The data analysis indicated also that there were no relationships between science faculty’s age, academic rank, nationality, country of graduation and years of teaching experience and their concerns in adopting BL in their teaching, so the null hypotheses 1.2-7 were accepted (There are no statistically significant differences between Science faculty’s age and their concerns in adopting BL, there are no statistically significant differences between Science faculty’s academic rank and their concerns in adopting BL, there are no statistically significant differences between Science faculty’s nationality and their concerns in adopting BL, there are no statistically significant differences between Science faculty’s content area and their concerns in adopting BL, there are no statistically significant differences between Science faculty’s country of graduation and their concerns in adopting BL and there are no statistically significant differences between Science faculty’s years of teaching experience and their concerns in adopting BL). The data analyses for research question two revealed that there was a statistically significant difference between science faculty’s use of technology in teaching by department and their attitudes towards technology integration in the Science curriculum. Lambda MANOVA test result was sig =.019 at the alpha = .05 level. Follow up ANOVA result indicated that Chemistry department was significant in the use of computer-based technology (sig =.049) and instructional technology use (sig =.041). Therefore, null hypothesis 2.1 was rejected (There are no statistically significant differences between science faculty’s attitudes towards technology integration in the Science curriculum and faculty’s use of technology in teaching by department). The data also revealed that there was no statistically significant difference (p<.05) between science faculty’s use of technology in teaching by department and their instructional technology use on pedagogy. Therefore, null hypothesis 2.2 was accepted (There are no statistically significant differences between science faculty’s perceptions of the effects of faculty IT use on pedagogy and faculty’s use of technology in teaching by department). The data also revealed that there was a statistically significant difference between science faculty’s use of technology in teaching by department and their professional development needs in adopting BL. Lambda MANOVA test result was .007 at the alpha = .05 level. The follow up ANOVA results showed that the value of significance of Science faculty’s professional development needs for adopting BL was smaller than .05 in the Chemistry department with sig =.001 in instructional technology use. Therefore, null hypothesis 2.3 was rejected (There are no statistically significant differences between Science faculty’s perceptions of technology professional development needs and faculty’s use of technology in teaching by department). Qualitative measures included analyzing data based on answers to three open-ended questions, numbers thirty-six, seventy-four, and seventy-five. These three questions were on blended learning concerns comments (question 36, which had 10 units), professional development activities, support, or incentive requested (question 74, which had 28 units), and the most important professional development activities, support, or incentive (question 75, which had 37 units). These questions yielded 75 units, 23 categories and 8 themes that triangulated with the quantitative data. These 8 themes were then combined to obtain overall themes for all qualitative questions in the study. The two most important themes were “Professional development” with three categories; Professional development through workshops (10 units), Workshops (10 units), Professional development (5 units) and the second overall theme was “Technical support” with two categories: Internet connectivity (4 units), and Technical support (4 units). Finally, based on quantitative and qualitative data, the summary, conclusions, and recommendations for Taibah University regarding faculty adoption of BL in teaching were presented. The recommendations for future studies focused on Science faculty Level of Use and technology use in Saudi universities.
Keywords: Professional Development; Blended Learning; Concerns; Education, Technology (0710)